Emotional regulation of preschool teachers: scoping review protocol (Research, Society and Development, 2022)
This study considered the importance of emotional regulation of the preschool teacher and how this directly influences mental health, performance, teacher performance, student learning, teacher-student relationship, and that emotional regulation is present in intervention and training programs aimed at this public. From this, the literature scoping review method was used. This is a research protocol based on the recommendations of the Joanna Briggs Institute (JBI) manual, following the Preferred Reporting Items for Systematic and Meta-Analyses-Extension for Scoping Reviews (PRISMA-ScR) checklist, which aims to map what the research of the last 5 years has evidenced on the subject. To this end, the goal of this protocol is to map the literature regarding preschool teachers' emotion regulation. For this, consultations will be made in 3 databases: Periódicos Capes, PsycInfo and Google Acadêmico, using the descriptors emotional regulation, teachers, kindergarten and preschool. The selection of studies will be made by two independent researchers. For the interpretation of the results, mapping will be carried out, which consists of a previous survey of the key themes presented in the articles' results, the grouping of this information, the identification of links between the points, and the synthesis of the studies, with the purpose of classifying and reclassifying the material produced according to the scope review question.